Mathematical Models for Quantitative Assessment of Bioluminescence Resonance Energy Transfer: Application to Seven Transmembrane Receptors Oligomerization - Drinovec, Luka; Kubale, Valentina; Nøhr Larsen, Jane; Vrecl, Milka (Frontiers in Endocrinology, 2012)
The idea that seven transmembrane receptors (7TMRs; also designated G-protein coupled receptors (GPCRs)) might form dimers or higher order oligomeric complexes was formulated more than 20 years ago and has been intensively studied since then. In the last decade, bioluminescence resonance energy transfer (BRET) has been one of the most frequently used biophysical methods for studying 7TMRs oligomerization. This technique enables monitoring physical interactions between protein partners in living cells fused to donor and acceptor moieties. It relies on non-radiative transfer of energy between donor and acceptor, depending on their intermolecular distance (1–10 nm) and relative orientation. Results derived from BRET-based techniques are very persuasive; however, they need appropriate controls and critical interpretation. To overcome concerns about the specificity of BRET-derived results, a set of experiments has been proposed, including negative control with a non-interacting receptor or protein, BRET dilution, saturation and competition assays. This article presents the theoretical background behind BRET assays, then outlines mathematical models for quantitative interpretation of BRET saturation and competition assay results, gives examples of their utilization and discusses the possibilities of quantitative analysis of data generated with other RET-based techniques.